Transesterifikasi In situ Produksi Biodiesel Dengan Variasi Massa Bahan Baku Terhadap Karakteristik Biodiesel - Syafitri, Nadhatul; Mustikaningrum, Mega (Universitas Muhammadiyah Gresik, 2024)
Biodiesel is one of the promising alternative fuels, environmentally friendly, and has no adverse effects on health. In this study, biodiesel production was carried out using the in situ transesterification method. The raw material used was mahogany seeds with variations in raw material mass of 10 grams and 20 grams. The catalyst used was KOH with methanol as the solvent and n-hexane as the co-solvent. In situ transesterification was performed at a reaction temperature of 65°C, stirring speed of 400 rpm, and a reaction time of 40 minutes. The research results show that the mass of the raw material affects the biodiesel yield. At a raw material mass of 10 grams, a yield of 70.09% was obtained, while for a raw material mass of 20 grams, the yield was 82.00%. The biodiesel analysis results show that the density values for the 10-gram raw material mass variation are 0.8512, and for the 20-gram raw material mass variation, it is 0.8556. The water content is 1.46%, and the free fatty acid (FFA) content is 0.76 mg KOH/gram for the 10-gram raw material mass variation and 0.675 mg KOH/gram for the 20-gram raw material mass variation. The results of the biodiesel characteristic tests meet the SNI 7182:2015 standard.